Diffusion of chromium and impurity absorption in ZnS crystals - Nitsuk, Yu.A. (Functional Materials, 2013)
ZnS:Cr single crystals obtained by diffusion doping are investigated. The spectra of optical density in the range of energies 0.3–3.8 eV are investigated. The chromium concentration in the studied crystals is determined using the magnitude of the shift of the absorption edge. Optical transitions determining the impurity absorption spectrum of ZnS:Cr single crystals are identified. The diffusion profile of Cr impurity is determined by measuring the relative optical density of crystals in the visible spectral region. At first, the diffusivities of Cr in ZnS crystals are calculated for temperatures of 1170–1320 K. At 1270 K, the diffusivity of Cr is 8· 10⁻¹⁰ cm²/s.